GERAKAN “FEMINISME HURA-HURA” MARI JEUNG REBUT KEMBALI DALAM VIDEO MUSIK TIKA AND THE DISSIDENT (STUDI SEMIOTIKA) - Regelinda Janggat, Martha Gloria; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 2 (2019), 2019)
ABSTRACT   This research titled Gerakan “Feminism Hura-Hura" Mari Jeung Rebut Kembali di Video Musik Tika and The Dissident (Studi Semiotika). In 2016 Tika and The Dissidents released a single called “Tubuhku Otoritasku" and Mari Jeung Rebut Kembali with collaborators making the music video that shows the freedom expression and had a big role in perceiving and influencing audience towards the mindset of women in society. The purpose of this research is to know how the movement of feminism in “Tubuhku Otoritasku” music videos. The type of this research is qualitative research with a constructivist paradigm and using approach analysis of Charles Sanders Peirce’s semiotic. The data source used in this research consists of primary data form the scene, background, or lyrics and secondary sources are from the articles, websites, and publications. The result of this research is the radical feminist movement that can be seen in the music video Keywords: Feminism, Charles Sanders Pierce Semiotic’s, Tika and The Dissident Band